Freshwater Fish Breeding in Pulo Damar Village Using E-Business - Prastyo, Yogi; Juwaini, Ahmad (Universitas Ibn Khaldun, 2023)
Since the Covid-19 pandemic, public interest in raising freshwater fish has shown an increasing trend, considering that now many layers of people work at home so that raising freshwater fish has become an entertainment in itself. The purpose of this research is to change the mindset of the people in Pulo Damar Village, where technological, social, and cultural developments have led to many companies being established to achieve certain goals in meeting human needs. Electronic Business or E-Business is a transaction, buying and selling, business activity carried out through electronic devices or with the internet so that companies can directly interact with customers, suppliers and business partners. Freshwater fish are fish that are easy to maintain, freshwater fish cultivation does not need a large place and large capital, it can be done as a home business. Therefore, we can make this freshwater fish business an online business (e-business) so that this fish business is more increased and can reach a broad market.